Der Morgenkreis Klassenöffentlicher Unterricht zwischen schulischen und peerkulturellen Herausforderungen - Heinzel, Friederike (Pädagogische Fallanthologie, 2016)
Morning circles open the school day together in many primary school classes. They form practical forms of realizing the pedagogical intention to make it easier for pupils to start school every day and to promote social learning and pupil participation. The present case analysis enables vivid insights into the practice of the morning circle and the associated options for action and action problems for primary school children and teachers.